Counterpoint: Epidemiology's Dual Social Commitment—Science and Health. Issue 6 (16th December 2020) - Saracci, Rodolfo
Abstract: Matching epidemiology's aspirations to actual delivery of goods valuable for population health depends both on the scientific and operational capabilities of epidemiology and on the degree to which the goods meet its contract with society. Epidemiology's capabilities have advanced remarkably in recent decades, although research gaps have appeared during the current coronavirus disease 2019 (COVID-19) pandemic. Epidemiology's social contract reflecting a dual commitment to science and health could arguably be entirely met by producing research results under conditions variously described as objective, impartial, neutral, or independent and handing such results to decision makers and the public at large. However, a closer examination shows that those four terms address sharply distinct issues, with distinct practical implications, and that the epidemiologist responsibility is de facto involved beyond providing research results. Hence the epidemiologist's engagement should encompass arguing from a science-for-health viewpoint and proactively driving the results into decision processes on public health issues.